Prosecuting domestic violence a philosophical analysis - Dempsey, Michelle Madden, 1970- (Oxford : Oxford University Press, 2009)
This text provides a philosophical investigation of the criminal prosecution of domestic violence. It features a theoretical framework for understanding ongoing debates regarding the criminal justice system's response to domestic violence.
Series from dust jacket.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Family violence -- Law and legislation -- Philosophy; Feminist jurisprudence